Population Structure of Phytophthora ×alni on a Local Scale and Its Temporal Development - Pecka, Štěpán; Koukol, Ondřej; Šrámková, Gabriela; Zahradník, Daniel; Prospero, Simone; Štochlová, Petra; Černý, Karel (Phytopathology, 2025)
Within Phytophthora alni, an invasive pathogen of alders (Alnus spp.), three species have been identified. The most frequent and pathogenic species is P. ×alni. It has a variable intraspecific structure, with the dominance of the Pxa-1 genotype and the presence of dozens of rare genotypes (in most cases derived from Pxa-1). Its local populations are highly variable, and their population structure and development remain unknown. We compared two sets of strains isolated from identical sites during the epidemic (2005-2010) and post-epidemic (2020-2024) phases of the disease in the Vltava River basin (Czech Republic) and studied them using microsatellite marker analysis and fitness tests (sporangia production, growth, and virulence). We acquired 151 P. ×alni isolates of 23 multilocus genotypes. We found that during the post-epidemic phase, genetic diversity decreased, and the dominance and incidence of the Pxa-1 genotype increased. Only the dominant genotype (Pxa-1) was repeatedly isolated from the same sites, whereas the rare genotypes were replaced. During the post-epidemic phase, both the incidence of rare genotypes and the degree of their derivation from Pxa-1 decreased. The rare genotypes had lower fitness than Pxa-1 (the more changes there were, the worse the fitness was). These results allow us to hypothesize the evolution of local populations of P. ×alni in Europe, as the most pathogenic genotype, Pxa-1, will also prevail during the late phases of the disease and the risk of further damage to the surviving host populations will persist.
Keywords: Oomycetes; Forest Pathology; Ecology; Population Biology; Epidemiology; Genetics